Effects of Time Management Training on the Academic Achievement of Female High School Students - Asieh.Sadat Baniaghil; Maryam Eksir; Nasser Behnampour (Golestan University of Medical Sciences, 2021)
Background: Time management skill learning and identification are very effective in the study process, and can reduce the adolescentschr('39') waste of time and help them increase the academic achievement. The present study aimed to determine the effect of time management skill on the academic achievement of female students. Methods: This interventional study was a randomized controlled field trial. The statistical population consisted of all 2785 female second-grade high school students in 2017-2018 covered by health centers of Gorgan, Iran. Forty eligible students were selected and allocated into intervention and control groups. In the intervention group, a group counseling session of time management training was held for 6 hours in two days. A month after intervention, all students completed the questionnaire, and the studentschr('39') grade point average (GPA) of the first and second semesters were extracted in 2017-2018. To compare the academic achievement we used the Mann-Witny U test, paired t-test, and Wilcoxon test in SPSS-16. Results: The mean of the GPA of students in control group before and after intervention were 17.95±1.47 and 17.86±1.67, respectively (P=0.43). The GPA in the intervention group was 17.61±0.84 before intervention and showed an increase to 17.75±1.08 after the time management skill training; but the increase was not statistically significant (P=0.43). The results indicated a statistical significant difference in mean scores of 2 subscales; short-term planning and time attitude in the intervention group in comparison with the control group. Conclusion: Despite the fact that time management skill training did not lead to the academic achievement in students, it could improve the short-term planning. Since the follow-up of the present study was short-term, it needs time to improve planning and affecting the academic achievement. It is suggested to examine this assumption in longitudinal and long-term studies.